Eudesmanolides and Other Constituents from the Flowers of Wedelia trilobata. Issue 3 (5th March 2018) - Hui, Yang; Cao, Jian; Lin, Jing; Yang, Jian‐Ni; Liu, Ya‐Jun; Han, Chang‐Ri; Song, Xiao‐Ping; Dai, Chun‐Yan; Zhang, Xiao‐Peng; Chen, Wen‐Hao; Chen, Guang‐Ying
Abstract : Two eudesmane sesquiterpene lactones, wedetrilides B (1 ) and C (2 ), along with five known analogues (3 –8 ), an ent ‐kaurane diterpenoid (9 ), a steroid (10 ), as well as cinnamic acid derivatives (11 –13 ), were isolated from the flowers of Wedelia trilobata . Their structures were elucidated on the basis of extensive spectroscopic analyses and by comparison of their NMR data with those of related compounds. Furthermore, the structures of1 and3 –5 were confirmed by X‐ray single‐crystal diffraction analyses. Compounds4 and5 exhibited weak cytotoxic activities against the MCF‐7, HeLa, and A549 cell lines. Compounds3 –5 were also evaluated for their inhibitory effects against HIV lytic replication. Abstract :